Providing Rewards as an Effort to Grow Self-Confidence in Madrasah Ibtidaiyah Students - Alia Latifah; Ichsan Ichsan (Al-Aulad: Journal of Islamic Primary Education, 2023)
In the learning process there needs to be motivation so that students can improve their learning outcomes. By participating in learning activities, students are expected to be able to develop themselves socially, emotionally, intellectually, linguistically, morally and personally in the positive direction that everyone wants. This is inversely proportional to the current reality that there are still students who are shy or don't dare to express their thoughts in public.thus making students less confident when answering questions from the teacher so that rewards come out as reinforcement. This study aims to reveal the giving of rewards to students' self-confidence. The research method used is descriptive qualitative with data collection techniques in the form of interviews. The subject of this research is a class III teacher at MI Al-Mutaqin. The results of the study revealed that the application of rewards to students at the elementary school/Madarsah Ibtidaiyah level was given by the teacher in learning including giving verbal rewards. The reward given has the impact of growing students self-confidence in learning.Keywords: Confidence, Madrasah Ibtidaiyah, Reward